Access to Veterinary Drugs in Sub-Saharan Africa: Roadblocks and Current Solutions - Jaime, Glória; Hobeika, Alexandre; Figuié, Muriel (Frontiers in Veterinary Science, 2022)
Reducing antibiotic use in order to fight antimicrobial resistance (AMR) has become a major goal in animal health policies in the recent years. The focus is usually set on farmers’ and veterinarians’ practices and perceptions. However, drug use also results from the structures of supply, that is access to medicines and the functioning of the drugs market chain. Based on the scientific and grey literatures, we present an overview of the limits to the access to veterinary drugs in sub-Saharan Africa (SSA), as well as the international policy tools and setups that claim to improve it. We highlight roadblocks to access to drugs: the African market is dependent on imports, highly fragmented, insufficiently regulated. Its distribution infrastructures and services are weak and increasingly populated by private non-professional actors. The distribution system is dualized: small farmers are only supported by the state providing basic health advice and vaccines, while the commercial and industrial farming sector is largely unregulated. International institutions and initiatives have been developed to lower these barriers, but progress slowly, while pharmaceutical corporations gain ground rapidly in policymaking. Policies against AMR should focus more on the drug markets and take into account the diversity of farming systems within countries.